Analysis of Knowledge Level Regarding Dangerous Goods and Their Impact on Passenger Compliance at Komodo Airport, Labuan Bajo, East Nusa Tenggara - Anisa Fitriani; Desiana Rachmawati (CV. Rayyan Dwi Bharata, 2023)
The modes of transportation consist of land, sea and air transportation modes, the mode of transportation that is often used today is the air transportation mode. In using air transportation, one must know the factors that can threaten flight safety, one of which is the transportation of dangerous goods. The purpose of this study is to find out how the level of knowledge about dangerous goods and the effect of knowledge on compliance. In this study, researchers used quantitative methods using primary data. Primary data was obtained from distributing questionnaires to 100 respondents in the departure terminal area at Komodo Labuan Bajo Airport. Obtained data obtained were then analyzed using descriptive statistics on the scale range and simple linear regression test. The test results are processed using the SPSS program. The results of the descriptive research on the scale range show a high level of knowledge of 3.39 followed by a high compliance score of 3.51. The results of the simple linear regression test showed a significance value of 0.000 0.05, indicating that H0 was rejected and Ha was accepted. From the results of the study it can be concluded that the level of knowledge of passengers regarding dangerous goods is high and followed by high compliance.